Effects of Zuojin pill on depressive behavior and gastrointestinal function in rats with chronic unpredictable mild stress: Role of the brain–gut axis. (23rd May 2020) - Wang, Tao; Yan, Yan-Feng; Yang, Lu; Huang, Yu-Zhen; Duan, Xin-Hui; Su, Kun-Han; Liu, Wan-Li
Abstract: Ethnopharmacological relevance: Zoujin pill (ZJP), a medication used to treat gastrointestinal disorders since the 15th Century in China, have been reported to exert anti-depressant effects in various models. Study aim: To assess the effects of ZJP on gastrointestinal function and depressive behavior in rats under chronic unpredictable mild stress (CUMS), and to examine the underlying mechanisms related to brain–gut axis. Methods: The rats suffered the stressor once daily for 5 weeks. ZJP (0.6 and 1.2 g/kg) and fluoxetine (15 mg/kg) as positive control were administered to the rats through gastric intubation once daily for 5 consecutive weeks. The anti-depression effects were compared by performing sucrose preference tests and open field tests. Gastrointestinal motility was investigated by determining the gastrointestinal transit rate and by electrogastrogram. The serum levels of the gastrointestinal hormone (GAS, MOT, VIP, SP), inflammatory cytokine (IL-1β, IL-6;, TNFα) and glucagon-like peptide-1 (GLP-1) were assayed by enzyme-linked immunosorbent assay. For monoamine neurotransmitters (NE, 5-HT, DA), the levels were determined by high-performance liquid chromatography and electrochemical detection in conjunction, which was applied on the samples taken from the hypothalamus, hippocampus, and striatum. Results: The depression-like symptoms among rats under CUMS were significantly relieved by ZJP administration (0.6 and 1.2 g/kg). Gastrointestinal motility was also improved by restoring gastric electrical rhythm and promoting gastrointestinal propulsion. The ZJP at 0.6 g/kg dosage obviously up-regulated 5-HT and DA levels in hippocampus. The ZJP at 1.2 g/kg dosage could increase 5-HT and DA levels in hypothalamus, striatum, and hippocampus, while down-regulated the NE level in hypothalamus and hippocampus. ZJP also reversed the alterations in serum gastrointestinal hormones. Furthermore, treatment with ZJP significantly reduced levels of IL-1β, IL-6 and TNF-α and increased serum GLP-1 compared with the CUMS group. Fluoxetine also exerted similar anti-depressant effects in the absence of effects on gastrointestinal motility and the levels of serum hormone, inflammatory cytokine and GLP-1. Conclusion: ZJP imposed anti-depressant and gastrointestinal regulating functions in rats under CUMS, suggesting potential clinical application. . Graphical abstract: Image 1